2011
DOI: 10.3109/00365521.2011.638391
|View full text |Cite
|
Sign up to set email alerts
|

The enteroendocrine “letter cells” – time for a new nomenclature?

Abstract: The endocrine cells of the gastrointestinal (GI) tract and the pancreas, referred to as the enteroendocrine cells, secrete a large variety of peptides and amines that regulate functions of the digestive tract itself and of distant organs. Taken together, the enteroendocrine cells form the largest system of endocrine cells in the body, presently comprising 16 cell types. Many of them have been named after letters of the alphabet, but the names are only occasionally related to morphological or functional charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…The present review outlines the evidence that a majority of EECs contain several hormones and that the one cell-one hormone concept is untenable, as other authors have also concluded (Helander and Fändriks 2012; Drucker 2015; Gribble and Reimann 2016). We also review evidence that, at a subcellular level, hormones are commonly concentrated in separate vesicles.…”
Section: Introductionmentioning
confidence: 85%
“…The present review outlines the evidence that a majority of EECs contain several hormones and that the one cell-one hormone concept is untenable, as other authors have also concluded (Helander and Fändriks 2012; Drucker 2015; Gribble and Reimann 2016). We also review evidence that, at a subcellular level, hormones are commonly concentrated in separate vesicles.…”
Section: Introductionmentioning
confidence: 85%
“…ECs are a highly specialized mucosal cell subpopulation which accounts for 16 distinct cell types and form the largest and probably most important diffuse endocrine systems in the body, which is responsible for many functions, including regulation of digestion, motility, and food intake in fishes (Ahlman & Nilsson, ; Takei & Loretz, ; Helander & Fändriks, ). In teleost fishes, these peptide hormones produced by the gut also act as an important peripheral sensory information source to hypothalamic center involved in feeding intake (reviewed by Volkoff, ).…”
Section: Introductionmentioning
confidence: 99%
“…GLUT2 is expressed in enteroendocrine cells, especially in L-cells [5]. L-cells express nutrient transporters and receptors that can sense luminal nutrients at their apical membrane and thereby influence their own functions [6], [7]. Enteroendocrine cells are scattered in the intestinal epithelium and constitute the largest population of hormone-producing cells of the body.…”
Section: Introductionmentioning
confidence: 99%